2020
DOI: 10.1108/jibr-01-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of foreign portfolio flows to Indian debt market

Abstract: Purpose The volatile nature of foreign portfolio flows, especially flows into debt market, has large implications on financial and macroeconomic stability in recipient countries. It is necessary to identify the main drivers of portfolio investments in bond market of developing economies to design effective policies to enhance resilience of the economy and help in managing capital flow volatility. The determinants of foreign portfolio investment to Indian equity market have been examined in literature, but flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The studies by Persson and Svensson (1989), Garg and Dua (2014) reveal the significant negative impact of exchange rate on FPI. To the contrary, Osemene and Arotiba (2018), and Gupta and Ahmed (2020) document the significant positive effect of exchange rate on foreign portfolio investment inflows. Liquidity affects the equity prices in any country, which alternatively have an impact on foreign investment.…”
Section: Determinants Of Foreign Investment In Pakistanmentioning
confidence: 97%
“…The studies by Persson and Svensson (1989), Garg and Dua (2014) reveal the significant negative impact of exchange rate on FPI. To the contrary, Osemene and Arotiba (2018), and Gupta and Ahmed (2020) document the significant positive effect of exchange rate on foreign portfolio investment inflows. Liquidity affects the equity prices in any country, which alternatively have an impact on foreign investment.…”
Section: Determinants Of Foreign Investment In Pakistanmentioning
confidence: 97%
“…Global empirical research has produced conflicting results regarding how foreign direct investment affects the volatility of the securities market. Studies by Singhl and Mohan (2020); Ameer, Xu and Sohag (2021); Heng et al (2021); Lee and Cho (2017); Gupta and Ahmed (2019) Bhasin and Kapoor (2019) reveal considerable effects, whilst others show insignificant effects. The findings are contradictory, which calls for additional research to be done in the current study to determine how foreign direct investment outflow affects the volatility of the securities market at the NSE in Kenya in an effort to close the knowledge body's current gap.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The long term coefficients showed a decline in the exchange of stock market volatility. Additionally, Gupta & Ahmed (2019) in India discovered that an increase in FDI has a significant impact on stock market fluctuations there, and (Alawi, 2019) in Saudi Arabia showed that FDIO contributes to the stock market, leading to the conclusion that FDI has a significant and favorable impact on stock price volatility.…”
Section: Panel Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation